Environmental Microbial Contamination during Cystic Fibrosis Group-Based Psychotherapy - Rossitto, Martina (Int J Environ Res Public Health, 2021)
Living with cystic fibrosis (CF) exposes patients to the risk of developing anxiety and depression, with therapeutic compliance reduction, hospitalization increase, and quality of life and health outcomes deterioration. As pulmonary infections represent the major cause of morbidity and mortality in patients with CF, environmental contamination due to droplet dispersion and the potential transmission from environment to such patients should be prevented. Therefore, in-person contact, including group-based psychotherapy, are strongly discouraged. Nevertheless, group sharing of disease-related experiences represents a way to recover the inner resources essential for dealing with a chronic pathology. Keeping in mind the guidelines for infection control, the aim of this study is to evaluate the risk of the dissemination of microorganisms in a restricted environment where patients with CF attend group psychotherapy sessions. Five patients, selected according to their microbiological status, attended 32 group-based psychological/psychoanalytic meetings. Before each session, they were asked to observe the infection control recommendations. Microbiological environmental monitoring (MEM) has been performed to evaluate both air and surface contamination. As reported, a strict observation of standard precautions allows one to avoid environmental contamination by pathogens of the CF respiratory tract. Although infection control guidelines discourage group-based psychological/psychoanalytic interventions, our observations report the feasibility and safety of group psychotherapy when strict precautions are taken.